2021
DOI: 10.3390/su13115890
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Enhancement Effects of Biochar on Wheat Growth and Yield under Arid Field Conditions

Abstract: Nitrogen (N) losses are prevalent under South East Asia’s due to high N fertilizer inputs, but low N fertilizer use efficiency. This leaves a large quantity of reactive N at risk of loss to the environment. Biochar has been found to reduce N losses across a variety of soil types, however, there is limited data available for semi-arid climates, particularly at a field-scale. Herein we present an exploration of the biological and chemical enhancement effects observed of a cotton stalk-based biochar on wheat grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 73 publications
3
29
0
Order By: Relevance
“…However, the increase in the OM-bound metal fraction due to the use of GB was dependent on the application level and pyrolysis temperature. These results are compatible with those obtained by [11,51]. They indicated that biochar application caused an increase in the metal fraction bound to the organic matter.…”
Section: Metal Mobility and Redistributionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the increase in the OM-bound metal fraction due to the use of GB was dependent on the application level and pyrolysis temperature. These results are compatible with those obtained by [11,51]. They indicated that biochar application caused an increase in the metal fraction bound to the organic matter.…”
Section: Metal Mobility and Redistributionsupporting
confidence: 92%
“…Over the past few decades, many methods have been used as a new tool to overcome the seriousness of the pollutants in contaminated soil, including stabilizing, drilling, dumping, soil washing, and electro carbons [7,8]. The use of organic or inorganic materials for stabilizing HMs is considered a faster, more effective, and environmentally friendly management technique that reduces their mobility and bioavailability by transforming them into unavailable forms in agricultural soils [1,4,[9][10][11]. Among organic amendments, biochar is a carbon-rich amendment produced through the pyrolysis of the biomass [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grain formation of wheat occurs during March at both study regions, under either semi-arid or arid climatic conditions. Usually, mid-March high temperature currently has a negative impact on grain size and ultimately on grain yield, as it has also been depicted in previous studies under rainfed climatic conditions [38][39][40][41][42]. In the future, March could have worse effects than the current conditions on the final grain yield of wheat.…”
Section: Future Climate and Wheat Grain Yieldmentioning
confidence: 65%